Matriculation 2005. Photo 022 - Loeb, Brian (Tufts Archival Research Center, 2008)
Matriculation 2005. Students moving in to their rooms in Wren Hall, Hill Hall and Metcalf Hall. Includes Orientation Coordinator Kate Drizos, LA '06.